Dramartugi Analysis and Structural Functionalism in the Creation of Halal Tourism Destinations in Indonesia - Moch. Zainuddin; Nur Ahid (ADP Publisher, 2024)
Halal tourism in Indonesia is growing rapidly, supported by its huge potential as a country with the largest Muslim population. In addition to driving economic growth, this sector strengthens Indonesia's image as a Muslim-friendly destination. This article analyzes the development of halal tourism destinations through dramaturgy and structural functionalism approaches, highlighting the role of local culture and the integration of tourism elements. Using literature and field data, this study identifies strategies, challenges, and opportunities to create a sustainable destination. This article also provides recommendations for stakeholders to optimize halal tourism as part of inclusive economic development. This research uses a descriptive-analytical qualitative approach based on literature study to analyze the development of halal tourism in Indonesia through the perspective of dramaturgy and structural functionalism. This study integrates dramaturgy and structural functionalism to analyze the development of halal tourism in Indonesia. Dramaturgy sees the destination as a